Retraction Note: The melanocortin signaling cAMP axis accelerates repair and reduces mutagenesis of platinum-induced DNA damage - Stuart G. Jarrett; Katharine M. Carter; Brent J. Shelton; John A. D’Orazio (Scientific Reports, 2021)
Editor's Note: this Article has been retracted; the Retraction Note is available at https://doi.org/10.1038/s41598-020-80467-y .